A Rapid Assessment of Annual Grassland Fire using Remote Sensing and GIS in Keibul Lamjao National Park, Manipur - Pebam, Rocky; Raju, P. L. N. (Indian Forester, 2019)
This paper analysed the pattern and extent of controlled fire in the floating grasslands of Keibul Lamjao National Park, Manipur, which is home to the endemic and endangered brow antlered deer (Rucervus eldi eldi). The grassland is controlled burnt every year as a part of park management. Sometimes the fire spreads extensively. The extent of the fire in 2017 was analysed using remote sensing data utilizing imageries from Indian Remote Sensing satellites and Landsat data. The fire scars were also compared with NASA’s VIIRS active fire pixel data pertaining to the period. About 53.38% of the total grassland area of the park had been effected by fire. The time-series (from 2001 to 2017) analysis of annual fires in the park showed that on an average about 300 to 350 ha of the park was burnt every year with the highest area being in 2017, followed by 2009. Considering the potential ecological impact of this annual practice, some new management strategies which will be ecologically sound, economically feasible and technically simple have been suggested for improving the habitat condition of the park for better survival of the endemic deer.